The Effects of WiFi Network (2.45 GHz) on Rats with Induced Stroke Associated with an Increased Risk of Heart Attack - Montzeri, Alireza; Pooladi, Mehdi; Odoumizadeh, Mohsen; Nazarian, Niloofar; Karani, Soheila (Archives of Advances in Biosciences, 2019)
Introduction: Stroke and heart attack are the most common causes of death among humans. Troponin I, Creatine Kinae-MB (CK-MB) and Lactate Dehydrogenase (LDH) are the diagnostic markers of heart attack which can also be used as high risk biomarkers. WiFi is a cheap common technology which exposes its users to a spectrum of electromagnetic waves. Can weak electromagnetic waves affect human health? Materials and Methods: In this study, stroke in rats has been induced, and then they were exposed to WiFi waves (2.45 GHz) and finally were examined for the risk of heart attack through analyzing three enzyme biomarkers related to heart attack (Troponin I, CK-MB and LDH). Results: This study’s results confirm WiFi’s biological effects and shows WiFi’s contribution in stroke. WiFi2.45GHz exposure affects three cardiac enzyme markers of heart attack (LDH, Troponin I and CK-MB), considering the current data on WiFi exposure effects on the brain, heart and related enzymes. Conclusion: Some of the WiFi wave’s cellular targets include cell membrane, cellular proteins and enzymes. Despite all the data and reports on biological effects of electromagnetic fields, the range and rate of these effects has not yet been determined.